Hypertension, socioeconomic status and depressive and anxiety disorders: a cross-sectional study of middle-aged and older Chinese women - Bo Song; Xueyin Wang; Xu Wang; Di Gao; Xiaosong Zhang (BMJ Open)
Objectives To investigate the association of hypertension with depressive and anxiety disorders in middle-aged and older Chinese women, and to further assess whether the association was influenced by socioeconomic status (SES).Design Nationwide cross-sectional study.Setting Six provinces of the eastern, central and western regions of China.Participants Women aged 40–70 years were included by a multistage stratified random cluster sampling in 2018 (N=9900).Primary outcome measures Depressive and anxiety disorders were measured by the Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7, respectively. Logistic regression models were used to evaluate the OR and 95% CI for hypertension and the odds of depressive and anxiety disorders.Results 18.5% of participants reported having hypertension; 20.9% and 15.3% of women experienced depressive and anxiety disorders, respectively. After adjusting for potential confounders, women diagnosed with hypertension were more likely to have depressive (OR=1.27, 95% CI 1.11 to 1.45) and anxiety disorders (OR=1.48, 95% CI 1.28 to 1.71) than those without hypertension. Stratified analyses demonstrated that hypertension was significantly associated with higher odds of depressive disorders in women living in rural areas (OR=1.34, 95% CI 1.13 to 1.59), with lower levels of education (OR=1.28, 95% CI 1.12 to 1.46) and with average monthly household income <¥3000 (OR=1.33, 95% CI 1.12 to 1.59), while hypertension was significantly correlated with increased odds of anxiety disorders in women living in urban (OR=1.41, 95% CI 1.12 to 1.79) and rural areas (OR=1.53, 95% CI 1.27 to 1.84), with lower levels of education (OR=1.47, 95% CI 1.27 to 1.70), and with average monthly household income <¥3000 (OR=1.45, 95% CI 1.20 to 1.75) and ≥¥3000 (OR=1.49, 95% CI 1.18 to 1.86).Conclusions Hypertension was associated with increased odds of depressive and anxiety disorders among middle-aged and older women, especially in those with low SES. Effective strategies and actions for identification and management of hypertension and depressive and anxiety disorders are needed.